Edukasi Kesehatan Reproduksi Pada Remaja di SMAN 5 Palu - Diana Towidjojo, Vera; Sari, Puspita; Asrinawaty, Andi Nur (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
Adolescents need an understanding of reproductive health to reduce and avoid the dangers of reproductive health disorders. This activity aims to increase the knowledge of young women about reproductive health. The method was a learning model to increase understanding of reproductive health. Participants were 100 students of SMAN 5 Palu who were randomly selected. Most of the students have good knowledge and understanding of reproductive health and use various sources to obtain information on reproductive health.